Model-driven methodologies for pervasive information systems development - Fernandes, José Eduardo (2010)
This paper intends to introduce the concept of pervasive information systems (PIS) and the issues that arise from the software development for pervasive information systems. The model driven approach is generally described and its benefits to the software design are identified. Finally, some future directions for the usage of model driven methodologies within the development of PIS are highlighted, presenting some specific problems that nowadays that kind of methodologies have not yet been able to overcome.